2017
DOI: 10.1099/jmmcr.0.005131
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella spp. infections in Gran Canaria, Spain: retrospective analysis of 31 cases and a literature review

Abstract: IntroductionShewanella spp. can cause severe skin and soft-tissue infections, gastrointestinal infections, otitis and bacteraemia, generally upon contact with seawater or consumption of raw seafood. Recently, a new condition termed ‘patera foot’ characterized by acute skin and soft-tissue infection has been described in irregular immigrants arriving to the Canary Islands, Spain, in rudimentary boats. Most infections are caused by a single species, Shewanella algae. The improvement of the diagnostic capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…e organism was first classified in 1990 by Simidu et al [1], emended by Nozue et al [2], and described as a Gramnegative, motile bacillus, with hydrogen sulfide production, exhibiting hemolysis on sheep blood agar. S. algae is found in marine environments throughout the world and has been linked with both human and marine animal infections [3,4]. Currently, there are at least three other Shewanella species found in clinical specimens and S. algae accounts for the majority of isolates from humans [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…e organism was first classified in 1990 by Simidu et al [1], emended by Nozue et al [2], and described as a Gramnegative, motile bacillus, with hydrogen sulfide production, exhibiting hemolysis on sheep blood agar. S. algae is found in marine environments throughout the world and has been linked with both human and marine animal infections [3,4]. Currently, there are at least three other Shewanella species found in clinical specimens and S. algae accounts for the majority of isolates from humans [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Shewanella are ubiquitously distributed in marine and freshwater environments, including deep-sea and polar regions, with some species being part of the microbiota of aquatic animals. One species, S. algae , is considered to be an emergent human pathogen (Martín-Rodríguez et al, 2017), with a few additional species being occasionally pathogenic. While human infections are still relatively scarce, the number of case reports is raising quickly, which can be partly due to higher medical awareness and refined identification methods (Martín-Rodríguez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One species, S. algae , is considered to be an emergent human pathogen (Martín-Rodríguez et al, 2017), with a few additional species being occasionally pathogenic. While human infections are still relatively scarce, the number of case reports is raising quickly, which can be partly due to higher medical awareness and refined identification methods (Martín-Rodríguez et al, 2017). Recent human microbiome studies have reported the presence of Shewanella in association with disease (Flemer et al, 2017; Kalyana Chakravarthy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Shewanella sp. have been identified in microbiomes of animals and even humans (Tryfinopoulou et al, 2007;King et al, 2012;Dailey et al, 2016;Chen et al, 2017;Flemer et al, 2017), and some species have emerged as human pathogens (Janda and Abbott, 2014;Martin-Rodriguez et al, 2017;Yousfi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%